Descriptive Study of the Islamic Understanding of the South Elfule Buru Community - Basri, La; Rumrah, M. Tamin; Wahid, Bustamin; Mardliyah, Uswatul (Universitas Muhammadiyah Sorong, 2024)
The thinking of the Elfule community in viewing Islam is still primitive, namely without any in-depth study of the Koran and al-hadith. This view is still under the influence of traditional culture and leads to a conservative understanding. This study intends to explain the understanding of Islam in the Elfule community in South Buru Regency by looking at the concept of religious and social meaning. The method used is ethnography, by way of observation and interviews, then analyzed using qualitative descriptions based on interviews obtained in the field. The results of the study found that how low the religious thinking of the Elfule people was so that there were rules of worship for the Elfule people starting from the prohibition for newcomers to pray in traditional mosques. In addition, it is distinguished in each prayer line which must be occupied by religious leaders, village heads, community leaders who have an important role in the front row, while ordinary people are in the back row and are required to eat the robe (syar'i) for both men and women. In social life there is a separation between indigenous peoples and immigrants, but to maintain good relations, immigrant communities are involved in the process of customary traditions.